The Conclusion and Completion of the Gift in Sudanese Law: A Comparative Study (International Journal of Financial, Administrative and Economic Sciences, 2024)
The study addressed the subject of the conclusion and completion of the gift in Sudanese law, some Arab countries’ laws and Islamic jurisprudence. The study showed that the gift is concluded by an offer only and is not dependent on acceptance from the donee according to the Hanafi School, except for Zafar. According to the majority, the gift is concluded by an offer and acceptance, and the laws (Sudanese, Lebanese, Egyptian and Saudi) agree with the opinion of the majority. The study also showed that the gift of real estate is a formal contract in the laws (Egyptian, Lebanese and Saudi), and that the gift of movable property may be a formal contract if it is completed in the manner required by law, and it may be a real contract if it is completed by taking possession. Regarding the effect of seizure on the gift, the study showed a difference in the classification of seizure as a condition in the contract, as in Sudanese law it is a condition of completion, in the Hanafi school it is a condition of validity (and it was said a condition of completion), and in the Shafi'i and Hanbali schools it is a condition of obligation, but despite this difference the result in each is the same, as the contract is valid before seizure, but it is not executed - i.e. the ownership is transferred from the donor to the donee - and is not binding unless the donor voluntarily delivers the gifted thing to the donee, i.e. the donor has the option to take possession or not without being obligated to do so. The study also showed that seizure is a pillar in the gift of movable property in some of the laws referred to, which is consistent with the statement of Zafar from the Hanafis, who went on to say that seizure is a pillar in the gift.
Keywords: Conclusion of the Gift; Offer; Acceptance; Form; Completion of the Gift; Receipt